Environmental catalysis - Grassian, Vicki H (Taylor & Francis, 2005)
The study of environmental interfaces and catalysis is central to finding more effective solutions to air pollution and understanding the impact that pollution has on natural systems. Environmental Catalysis covers concepts, applications, techniques, and methods related to a broad range of topics in environmental catalysis, providing a mix of theory, computation, analysis, and synthesis throughout. Divided into three parts, the first focuses on surface adsorption and catalysis of airborne particles, including ice, dust, soot and mineral surfaces as well as particles in contact with ground water. The second treats catalysis as the key technology for the treatment of emissions and waste, focusing on catalytic converters and the role of various catalysts including the use of biocatalysts. The last section focuses on catalysis in engineered systems as applied to green chemistry, using of selective oxidation reactions, enzymes reactions, and reactions in alternative solvents as key examples.